Given: The function below:
![f(x)=2x](https://img.qammunity.org/2023/formulas/mathematics/high-school/nxm0bdtiaqhb8lyqfd1gg8jm3z874on33m.png)
To Determine: The interation with initial value of 1
When the initial value is 1, it means that x = 1
If x =1, we can determine f(1) by the substituting for x in the function as shown below:
![\begin{gathered} f(x)=2x \\ x=1 \\ f(1)=2(1)=2*1=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2vgqwbasj2xat27ofbifw39xk2t5o1sct5.png)
![f^2(1)=2^2*1=2*2*1=4](https://img.qammunity.org/2023/formulas/mathematics/college/r27ml7n44fifth7tf7pwr8dkdox6olixb4.png)
Part 1:
It can be observed that as the number of iterations grow, the number increase in powers of 2
This can be modelled as
![f^n=2^n*1=2^n](https://img.qammunity.org/2023/formulas/mathematics/college/s07g9z4ea7isgbaoqzn47fq094cz1q0ael.png)
![f^(10)=2^(10)*1=1024](https://img.qammunity.org/2023/formulas/mathematics/college/kvg4xvdjdm94gs4ez86mst3j4py5ig5vty.png)
Part 2:
If we repeat the process with an initial value of -1. As the number of iterations grows, the number can be modelled as
![\begin{gathered} f^(-n)=2^(-n)*1 \\ f^(-1)=2^(-1)*1=(1)/(2)*1=(1)/(2) \\ \text{For initial value of -2, we would have} \\ f^(-2)=2^(-2)*1=(1)/(2^2)*1=(1)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vjwiz6iqclvvj38hoso9xl0mrvoyq6fie1.png)
So, as the initial value decreases, it can be observed by the above calculations that the number would be decreasing by the the reciprocal of the power of 2.